Implementation of the Qur'an Surat Al-Isra' Version 23-25 in the Development of Muslim Family - Siti Mutiara Salsabila Karya Putri; Ajat Rukajat; Yayat Herdiana M (Universitas Muhammadiyah Enrekang, 2021)
The Qur'an is an inexhaustible source of educational pearls. In the Qur'an there are very many texts or verses that guide and educate humans, because the purpose of the Qur'an was revealed to guide and direct humans to the right path. This research is motivated by the attention of researchers who are interested in the study